Molecular Genetic Diversity of 12 Origanum vulgare subsp. hirtum Genotypes: EST-SSR Marker Analyses - TAN, Uğur; ARABACI, Olcay (ISPEC Tarım Bilimleri Dergisi, 2024)
Conducting a genetic diversity study on Origanum vulgare using genetic markers is important to investigate the genetic variability and evaluation of the population structure of the species. Genetic diversity of Origanum vulgare has been determined with various genetic markers among different subspecies. Studies on the genetic diversity of its one of the most well known and widely grown subspecies, Origanum vulgare subsp. hirtum, have revealed high intraspecific genetic variability among different individuals within the species. In Origanum vulgare subsp. hirtum, employement of a molecular marker, Expressed Sequence Tagged – Simple Sequence Repeat (EST-SSR), allow the identification of distinct genetic profiles that can assist in cultivar identification and the comprehension of the genetic relationships within species. The primary aim of this study was to investigate the genetic diversity and population structure of 12 Origanum vulgare subsp. hirtum (Istanbul oregano) genotypes using nine EST-SSR markers. These EST-SSR markers (OR09, OR10, OR12, OR13, OR14, OR27, OR32, OR40 and OR44) were resulted total nine different alleles within all populations. OR9 primer have shown one unique alleles, reflecting genetic distinctiveness within the population. A total number of three clusters were determined in dendongram analysis (Neighbor Joining). The Origanum vulgare subsp. hirtum individuals investigated in this study exhibited low genetic diversity, with low to medium genetic variation both within and among the five populations (A, B, C, D and E). This limited diversity is might be due to the isolation within and between populations and also small population size. Despite this, certain EST-SSR markers, specifically OR13 and OR40, have proven to be valuable markers for assessing genetic diversity. These markers can play a crucial role in further breeding programs for identifying new varieties within Origanum vulgare subsp. hirtum populations.